Nutritional status of under-five pulmonary tuberculosis patients before and after six-month therapy - Barita Sidabutar; Soepardi Soedibyo; Alan Tumbelaka (Indonesian Pediatric Society Publishing House, 2016)
Background Tuberculosis (TB) is a chronic infectious disease which remains a health problem throughout the world including in Indonesia. The implementation of directly observed treatment short- course (DOTS) strategy will hopefully increase patient's compli- ance, so that a minimum of 85% cure rate could be achieved. The success in coping with TB disease is expected to become one of factors that play role in providing a solution for malnutrition prob- lems in Indonesia, especially for those caused by TB. Objective The aim of this study was to determine the distribution of nutritional status of under-five TB patients before and after six - month therapy. Methods We reviewed under-five children with pulmonary TB vis- iting the Pediatric Pulmonology Outpatients Clinic of Cipto Mangunkusumo Hospital from January 1999 to December 2001. Results Using the weight-for-age (W/A) indices, from 279 patients, the proportion of well-, under-, and severe-malnourished status was 36.9%, 60.2%, and 2.9%, respectively, and after 6-month therapy it became 58.8%, 39.8%, and 1.4%, respectively. Conclusion After 6 months of therapy, the nutritional status of TB patients increased